KEMAMPUAN MENULIS KARANGAN ARGUMENTASI DENGAN MENGGUNAKAN MODEL THE POWER OF TWO SISWA KELAS XI SMA NEGERI 5 KOTA TERNATE - Winarti Teapon; Justam Wahab; Taib Abdullah (Cakrawala Bahasa, 2020)
Problems in this study are (1) How is the ability to write an argumentation by using the power of two students of class XI SMA 5 Kota Ternate? (2) How far is the ability to write an argumentation by using the power of two class XI students of SMA Negeri 5 Ternate? The purpose of this research is (1) To know how the ability to write argumentation by using the power of two students of class XI SMA 5 Kota Ternate. (2) To know how far the writing ability of argumentation by using the power of two model of class XI students of SMA 5 Kota Ternate. The method used in this research is descriptive quantitative method by using the formula percentage. The population in this study is the total students of class XI SMA Negeri 5 Kota Ternate, amounting to 120 students. While the sample research is part of the total population that is the overall class XI students SMA Negeri 5 Ternate as much as 30 students by 25%. The results of the research are: (1) The observations found in the students of grade XI SMA Negeri 5 Ternate, the teacher of Indonesian language study has done a good learning process in accordance with the application of curriculum and the development of learning syllabus in accordance with the standard contents in the Plan Implementation of Learning (RPP) to improve student learning outcomes. (2) The results of interviews found by researchers at the time of research data taken between researchers with subject teachers and students of class XI SMA Negeri 5 Ternate, that teachers have teaches students about learning writing argumentation and students can develop a good imagination to pour in the writing of argumentation.